Music, Fable, and Fantasy: Thomas D’Urfey’s Wonders in the Sun and the Eighteenth-Century Political Animal - Ladd, Heather (Lumen)

(untitled) (Canadian Society for Eighteenth-Century Studies / Société canadienne d'étude du dix-huitième siècle, 2020)
This article considers a strange, understudied work of eighteenth-century musical theatre, Thomas D’Urfey’s Wonders in the Sun (1706). This highly intertextual, generically heterogeneous comic opera is a pastiche of literary and performative modes and ultimately a machine for generating wonder; it draws on elements from Aristophanes’ The Birds, seventeenth-century masque and semi-opera, as well as the lunar fictions. The article situates this play not only within a history of literary wonder and stage spectacle, but within the English tradition of politicized animal fable. Discussing D’Urfey’s comic opera against selections from John Gay’s Fables, it argues that the utopian/dystopian animal in these imaginative satires reveals the period’s twinned fascinations with discovery and alterity, as well as emergent discomfiture with anthro- and Eurocentric Enlightenment beliefs.